Ustor: cloud storage system based on regenerating codes - Qing LIU; Dan FENG; Bai LI (Tongxin xuebao)
To ensure reliability of user's data, multiple clouds are responsible for storing the data. For purpose of mini-mizing storage cost and repair bandwidth, a method of utilizing functional regenerating codes(FRC) to encode data to several blocks, which are further distributed to different clouds, was proposed. In this way, amount of data downloaded through the network when data loss happens in a single cloud is cut down, and repair cost is cut down as well. This method was successfully applied in a cloud storage system Ustor. Observations can be drawn from the experimental re-sults: first, erasure coding guarantees data reliability, increasing 5%～10% response time compared with non-coding; sec-ond, speed of FRC encode, decode and repair are a little slower than Reed-Solomon(RS) code, and the time gap of en-coding 256MB by two codes is less than 0.5 seconds; third, compared with traditional RS codes, FRC reduces more than 25% data amount needed to download during a repair in the experiment.